A natureza constitucional material do duplo grau de jurisdição nos processos criminais: análise em relação aos julgamentos originários perante o Supremo Tribunal Federal - Silva Júnior, José Ailton da (2016)
The normal dissatisfaction of the human being when he is in face of something that is adverse, plus the fallibility of the people and an imperative of optimization and law security indicate to the existence of a natural right to a sentence review, that is called double degree of jurisdiction or right to an appeal. The investigation about this guarantee has important outlines when some legal frameworks begin to incorporate it verbatim even in their constitutions. Other fact that instigate the research is the insertion of the double degree of jurisdiction guarantee in the most important declaratory documents of human rights as the International Covenant on Civil and Political Rights, European Covenant on Human Rights, African Chart of Human Rights and, especially, for the Brazilian system, the American Covenant on Human Rights. Once the double degree of jurisdiction has been declared fundamental human right in the international ambit, the questioning about it unrestricted application in the criminal trials arises in the signatory countries of these legal instruments, including Brazil. This questioning is reinforced because, traditionally, in Brazil, all of the people which is originally processed for the Brazilian Supreme Court, and for the other Tribunals, have not guaranteed the right to an appeal. We have, in this way, some anomaly in the system: on one side, the double degree of jurisdiction internationally recognized as a fundamental human right; whereas, a State, which is known as a democratic state of law, denying the application of a fundamental human right in some criminal law proceedings that are sentenced in its jurisdiction. This situation is at the least uncomfortable and its analysis is necessary.